If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(2x-2)=6x+8-2x
We move all terms to the left:
-4(2x-2)-(6x+8-2x)=0
We add all the numbers together, and all the variables
-4(2x-2)-(4x+8)=0
We multiply parentheses
-8x-(4x+8)+8=0
We get rid of parentheses
-8x-4x-8+8=0
We add all the numbers together, and all the variables
-12x=0
x=0/-12
x=0
| 1x+10=26 | | 57=1+8a | | 7x⁴=63x² | | 9-2x=8x-1 | | (7x+4)+(5x+16)=180 | | 4a+8-2a-3=45 | | 25(2p+5)=5p+12.5 | | 10x+2=8–5x | | y-5.123=4.8 | | x-6+5(x=2) | | Y=-9+13x | | X+2+1.50x+9= | | –9–5(x–1)=–9x+8(2x–11) | | 8m-15=27 | | 10w-10=30 | | X+$2+$1.50x+$9= | | 3(6-7z)+19=-152 | | 2x+4=3(2x+1) | | 4(5+x)=14 | | 3(p+3=12 | | Y=-18x-11 | | 3x(2x+1)+5=2(3x+1)+5 | | 6(3y+6)=18y+36 | | 10z+12=5z-28 | | (3×+11)+(4x-15)=180 | | 4p/9+p/3-1/2=11/16 | | 2(4u-2)=-36 | | 4(3r-4)=3(r+9)-2 | | 3(2x+1)-2=8x+1-2x | | A=21x+1 | | x=52x+3-4x= | | -0.6m+1=7 |